2006
DOI: 10.1007/s10722-004-6149-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Slow Rusting Components in Pea (Pisum sativum L.)

Abstract: Three hundred and forty five accessions of pea of diverse origin, height, leaf types and disease reaction were screened for rust disease severity and area under disease progress curve (AUDPC). The frequency of slow rusting types in the tall, dwarf, early and late groups appeared comparable. Of the 345 accessions, forty-four genotypes were evaluated for disease intensity, which was converted into AUDPC, number of pustules/leaf and pustule size. Wide range of variation was found for these traits. The slow rustin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 4 publications
3
27
0
Order By: Relevance
“…The genotypes with higher AUDPC and PDI values are more susceptible to sheath blight than those with lower values. AUDPC and PDI values in the present study are quite similar to that observed by Chand et al (2006), Taheri et al (2007) and Adhipathi et al (2013).…”
Section: Discussionsupporting
confidence: 92%
“…The genotypes with higher AUDPC and PDI values are more susceptible to sheath blight than those with lower values. AUDPC and PDI values in the present study are quite similar to that observed by Chand et al (2006), Taheri et al (2007) and Adhipathi et al (2013).…”
Section: Discussionsupporting
confidence: 92%
“…These studies revealed that the majority of the studied pea genotypes were susceptible, though genotypic differences in the rust intensity described as of slow rusting type have been reported (Kumar et al 1994;Chand et al 2006) (Table 1). Slow rusting resistance against U. viciae-fabae has been characterised by measuring the area under the disease progress curve (AUDPC), the disease severity (DS), the number of pustules/leaf or infection frequency (IF) and the pustule size .…”
Section: Screening and Sources Of Resistancementioning
confidence: 94%
“…The correlation observed between DS values measured under field conditions during three growing seasons, and between DS and AUDPC was high (Barilli et al 2009b) suggesting that the final DS estimation on pea provides a feasible estimation of partial resistance. DS estimation Sohi et al (1974) PJ207508, PJ22211, EC109188 monogenic inheritance Pal et al (1979Pal et al ( , 1980 RPB-22, RA-10-5, RC-35-2 Abusaleha and Pal (1990) Pant P11, FC1, HUDP 16, JPBB 3, HUP 14 monogenic (putative Ruf ) inheritance Chand et al (2006); Kushwaha et al (2006) U. pisi IFPI3260, PI347321, PI347336, PI347347, PI343935, PI343965, PI347310 inheritance under study Barilli et al (2009a, b) needs less computation and is less time-consuming than assessing AUDPC, epidemic growth rate (r) or the first pustule appearance (t 0 ). The epidemic growth rate and the first pustule appearance were poor estimators of U. pisi partial resistance as they were less discriminating than the other parameters and showed a low correlation within experimental designs.…”
Section: Screening and Sources Of Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Several sources of incomplete resistance against U. viciae-fabae have been reported (Pal et al 1980;Xue & Warketin 2001;Vijayalakshmi et al 2005;Chand et al 2006;Kushwaha et al 2006). A single major gene (Ruf) has been reported as responsible for this partial resistance.…”
Section: Rusts (Uromyces Pisi and U Viciae-fabae Pers)mentioning
confidence: 99%